URBAN FORM AND SOCIAL PRACTICES IN THREE NEIGHBOR-HOODS OF COLLECTIVE HOUSING IN THE CITY OF OUM EL BOUAGHI, ALGERIA - Nadjar Sarra Ismahane; Mazouz Said (International Journal of Innovative Technologies in Social Science, 2024)
The aim of this article is to study the influence of urban form in different collective housing programs across three neighborhoods in the city of Oum El Bouaghi on user practices and social interactions. To understand the complex relationships and socio-spatial structure of neighborhoods, it is important to use mixed methods. This research is based on a combi-nation of two approaches: qualitative and quantitative. The latter is based on the space syn-tax method, using dedicated software called DepthMap©, specifically applying the visibility graph analysis (VGA). The qualitative approach is based on in-situ observation (static snap-shot method). The observation data from three neighborhoods were collected and synthesized on a map to superimpose them on that of the VGA. The results obtained from correlating observed social activities with syntactic measures show that urban form affects the use of outdoor spaces and can be considered a determining factor in social practices and interactions.